A review of potassium channels in bipolar disorder - Judy, Jennifer T.; Zandi, Peter (Frontiers in Genetics, 2013)
Although bipolar disorder (BP) is one of the most heritable psychiatric conditions, susceptibility genes for the disorder have yet to be conclusively identified. It is likely that variants in multiple genes across multiple pathways contribute to the genotype-phenotype relationship. Recent evidence from genome-wide association studies (GWAS) implicates an entire class of genes related to the structure and regulation of ion channels, suggesting that the etiology of BP may arise from a channelopathy. In this review, we examine the evidence for this hypothesis, with a focus on the potential role of voltage gated potassium channels. We consider evidence from genetic and expression studies, and discuss the potential underlying biology. We consider animal models and treatment implications of the involvement of potassium ion channelopathy in BP. Finally, we explore intriguing parallels between BP and epilepsy, the signature channelopathy of the CNS.